THEORETICAL ANALYSES OF EELS FROM AN N-TYPE INSB SURFACE - Inaoka, T; Newns, D; Egdell, R (1987)
Treating the conduction band carriers in n-type InSb as a semi-infinite degenerate electron gas we are able to account for characteristic variations with exciting beam energy of plasmon and phonon loss intensities and frequencies in HREEL spectra. The theory is free of adjustable parameters and introduces effects of electron gas screening at a surface in a natural way. To improve the agreement with experimental data it is necessary to take account of the non-parabolicity of the conduction band dispersion in InSb. © 1987 Elsevier Science Publishers B. V.